Alveolar bone healing in rats: micro-CT, immunohistochemical and molecular analysis (Journal of Applied Oral Science, 2022)
Alveolar bone healing after upper incisor extraction in rats is a classical model of preclinical studies. The underlying morphometric, cellular and molecular mechanism, however, remains imprecise in a unique study. Objectives: The aim of this study was therefore to characterize the alveolar bone healing after upper incisor extraction in rats by micro computed tomographic (Micro-CT), immunohistochemical and real-time polymerase chain reaction (RT-PCR) analysis. Material and Methods: Thirty animals (Rattus norvegicus, Albinus Wistar) were divided into three groups after upper incisors extraction at 7, 14, and 28 days. Micro-CT was evaluated based on the morphometric parameters. Subsequently, the histological analyses and immunostaining of osteoprotegerin (OPG), receptor activator of nuclear kappa B ligand (RANKL) and tartrate resistant acid phosphate (TRAP) was performed. In addition, RT-PCR analyses of OPG, RANKL, the runt-related transcription factor 2 (RUNX2), osteocalcin (OC), osteopontin (OPN), osterix (OST) and receptor activator of nuclear kappa B (RANK) were performed to determine the expression of these proteins in the alveolar bone healing. Results: Micro-CT: The morphometric parameters of bone volume and trabecular thickness progressively increased over time. Consequently, a gradual decrease in trabecular separation, trabecular space and total bone porosity was observed. Immunohistochemical: There were no differences statistically significant between the positive labeling for OPG, RANKL and TRAP in the different periods. RT-PCR: At 28 days, there was a significant increase in OPG expression, while RANKL expression and the RANKL/OPG ratio both decreased over time. Conclusion: Micro-CT showed the newly formed bone had favorable morphometric characteristics of quality and quantity. Beyond the RUNX2, OC, OPN, OST, and RANK proteins expressed in the alveolar bone healing, OPG and RANKL activity showed to be essential for activation of basic multicellular units during the alveolar bone healing.